Evaluation of an in vitro mouse testis organ culture system for assessing male reproductive toxicity. Issue 2 (21st December 2018) - Nakamura, Noriko; Sloper, Daniel T.; Del Valle, Pedro L.
Abstract : Background: Development of an in vitro system capable of producing mature sperm remains a challenging goal, with only few successes reported. Such a system, could be used to test agents for potential toxicity to the male reproductive system; to explore this, we exposed immature mouse testis fragments in culture to ethinylestradiol (EE), a well‐known testicular toxicant in vivo. Methods: Testis fragments from postnatal day 5 mice were cultured in Albumax I medium. After 24 hr of culture, fragments were treated with 0.01, 0.1 or 1 nM EE, then harvested after 20 days in culture and examined for histology or gene expression measures by quantitative PCR. Results: There was substantial variability between fragments in the degree of spermatogenesis observed. The percentage of seminiferous tubules containing any dead germ cells increased as a result of EE exposure in a dose dependent fashion. This was accompanied with a decreased percentage of tubules with round spermatids. Expression of estrogen receptor 1, cytochrome P450, family 11, subfamily a, and polypeptide 1 also was reduced, depending on the dose. Conclusion: These gene expression changes in the testis fragments are similar to those seen after animals have been exposed to EE. Gene expression changes in testis fragments are encouraging, but the variability across samples will need to be reduced for this in vitro system to become a generally applicable method for assessing testicular toxicants.